Towards building circular economy: A cross-cultural study of consumers' purchase intentions for reconstructed products. Issue 4 (15th November 2018) - Gaur, Jighyasu; Mani, Venkatesh; Banerjee, Pratyush; Amini, Mehdi; Gupta, Ritu
Abstract : Purpose: Extant literature provides insights about consumers' purchase intentions (PI) and willingness to pay for reconstructed products but does not capture cross-cultural differences. The purpose of this paper is to understand consumers' PI for reconstructed products in a cross-cultural setting for the development of circular economy. Design/methodology/approach: The sample includes consumers from two diverse societies (India and the USA). The authors conduct two sets of analyses in this paper. The first analysis attempts to identify the difference between the Indian and US consumers' PI for reconstructed products, who are residing permanently in their home countries. In the second analysis, the authors investigate the impact of socio-cultural norms on PI, for reconstructed products, of the Indian (USA) consumers relocated to the USA (India). In-depth interviews are conducted for data collection. Subsequently, data analysis was carried out using thematic analysis approach. Findings: The results indicate that US consumers: possess altruistic buying behavior; are eco-centric toward waste disposal; strictly follow the regulations and socio-cultural norms; and have harmony orientation toward nature. In contrast, Indian consumers: possess utilitarian buying behavior; demonstrate anthropocentric attitude toward waste disposal; do not necessarily follow the regulations; and have mastery orientation toward nature. Practical implications: At policy level, government in emerging economies should formulate regulations that promote the use of reconstructed products. At firm level, firms should exploit promotional and advertisement efforts to enhance awareness about reconstructed products. Originality/value: The study is an early attempt in the literature to capture cross-cultural differences for reconstructed products.